Pengajar Kredibel dan Mahasiswa Jujur: Literasi Ekonomi Tinggi? - Prakoso, Albrian Fiky; Kurniawan, Riza Yonisa; Ghofur, Muhammad Abdul (Universitas Pendidikan Ganesha, 2020)
Many students see that cheating during an exam is the most effective way to improve academic grades. Many of them do that because they think teaching the lecturer is less credible. This study aims to determine whether the credibility of lecturers and student dishonesty can affect the level of economic literacy of students. The number of respondents in this study amounted to 77 students and analyzed using a quantitative approach. The results showed that the higher the credibility of lecturers, the lower the academic cheating. The more credible the lecturer, the higher the economic literacy of students. However, it turns out that student academic cheating does not determine the level of economic literacy of students. The exciting thing from the results of this study is that the ability of lecturers to answer questions turns out to determine students' perceptions about the credibility of their lecturers. Still, when students call lecturers more credible, it makes students commit fraud.Â